PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KINERJA AUDITOR. STUDI PADA KANTOR AKUNTAN PUBLIK DI JAKARTA TIMUR - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This study examines the effect of competence and independence on the performance of auditors working in public accounting firms in the area of East Jakarta. Data obtained with a questionnaire of 32 samples and analyzed using regression analysis. Hypothesis testing using the t test and f test. The results of the study are competence and independence both partially and simultaneously affect the auditor's performance.